Impact of COVID-19 on the International Container Shipping Market: A Data-Driven Analysis of North America-Asia and West-East Coast America Routes - Xue Zhiping (SHS Web of Conferences)
This study examines the impact of the COVID-19 pandemic on the international container shipping market, focusing on the changes observed in the North America-Asia routes and the East and West Coast routes of the United States. The study analyzes market changes before and after the pandemic outbreak by collecting Shanghai Containerized Freight Index (SCFI) data from 2017 to 2022. Utilizing a Difference-in-Differences analysis, the research explores the pandemic’s effect on the SCFI index. The findings reveal that the SCFI index for the North American route increased significantly by approximately 6,807 points compared to the Asian route due to the pandemic. In contrast, the East Coast of the United States had a freight index 1,246 points higher than the West Coast, mainly due to decreased port efficiency and insufficient capacity during the pandemic. Additionally, the study identifies that severe port congestion and reduced efficiency in the United States further contributed to the rise in freight rates.